Foliar Application of Carnosine and Chitosan Improving Drought Tolerance in Bermudagrass - Tian Hao; Zhimin Yang; Jianfeng Liang; Jingjin Yu; Jun Liu (Agronomy, 2023)
Drought stress is one of the crucial factors affecting plant growth and development in turfgrass species, especially during the summer season. Exogenous plant growth regulators are an effective and convenient approach to mitigating the adverse effects of drought stress on plant growth. The objectives of this study were to reveal the effects of exogenous carnosine or chitosan on turf performance and physiological indexes in bermudagrass (Cynodon transvaalensis × C. dactylon) in response to drought stress. Bermudagrass was foliar sprayed with carnosine or chitosan, and dose-dependent effects on turf quality were observed under drought stress. Under drought stress, foliar application of either carnosine (0.03%) or chitosan (10 mg L−1) significantly increased turf quality, chlorophyll content, leaf relative water content, and decreased electrolyte leakage, malonaldehyde, and hydrogen peroxide content in comparison with untreated control in bermudagrass. Moreover, exogenous carnosine treatment significantly enhanced the activities of both catalase and peroxidase, but chitosan application only increased catalase activity. The results of this experiment were beneficial to the development of new plant growth regulators and would provide helpful insights for turf management under drought-stressed conditions.